Prevalence of group A rotavirus genotype G1P[8] in Chennai, South India - Daga, Nikita; Sankar, Jamuna; M.S., Sakeena Sadullah; Sankaranarayanan, V. S.; Srinivas, S.; Devaraj, H.; Devaraj, S. Niranjali (International Journal of Contemporary Pediatrics, 2016)
Background:Rotavirus is one of the significant causes of severe diarrhoea in children less than 5 years of age, worldwide. The objective of this study was to determine the distribution of the G and P genotypes of rotavirus seasonal variation and to monitor if there was any emerging genotype or unusual strain circulating among children with diarrhoea, age less than 5 years, in Chennai, India. Methods: 171 stool specimens were collected from children with moderate to severe diarrhoea admitted to hospital or outpatient wards from January to December 2013 and information was collected from patients for rotavirus vaccination status. Results:Out of the 171 stool specimens, 109 specimens were detected positive for rotavirus by using VIKIA rapid kit method. The G and P genotypes were identified by reverse transcription-hemi nested PCR. G1P[8] (63.30%) was the most prevalent strain observed. Other genotypes observed were G1P[4], G1P[6], G2P[4], G9P[4], G9P[8], G12P[6], G12P[8] and some mixed infections were also observed with different rotavirus strains such as G1P[4]P[8] and G1G2P[6]. Conclusions:In this study, out of 109 positive patients, 7 patients who were vaccinated with 2 doses of rotarix vaccine were also positive for different strains of rotavirus. Rotavirus diarrhoea was found to occur throughout the year with a peak in the month of July and mostly in children aged 0-24 months.